VD_FINDINFO HC / 2018 / 965 vom 25. Oktober 2018 - VD Tribunal cantonal (2018)
RADIATION DU RÔLE, PROCÈS DEVENU SANS OBJET, NOVA, MODIFICATION DE LA DEMANDE | 85a LP, 242 CPC (CH), 317 al. 1 CPC (CH), 317 al. 2 CPC (CH)